Effects of Shell Encapsulation on the Nonlinear Dynamics of a Microbubble Contrast Agent subjected to Acoustic Energy - Fatimah, Dzaharudin; Najihah, Mohd Ali; Erny Afiza, Alias; Ummu Kulthum, Jamaludin (EDP Sciences, 2018)
The effects of encapsulating a microbubble on the energy in oscillation and acoustic signature is investigated by solving the governing equations of motion. Numerical data obtained by solving these equations is used to explore the effects of shell on the harmonics of the bubble system. By encapsulating the microbubble with a shell, the bubble will be stiffer resulting in lower amplitude oscillations and an increase in the harmonics of the bubble system upon subjected to acoustic energy. This is desirable in triggering vascular permeability for drug/gene control and release in biomedical applications.